Correction: Thermoreversible crystallization-driven aggregation of diblock copolymer nanoparticles in mineral oil. Issue 3 (20th December 2018) - Derry, Matthew J.; Mykhaylyk, Oleksandr O.; Ryan, Anthony J.; Armes, Steven P.
Abstract : Correction for 'Thermoreversible crystallization-driven aggregation of diblock copolymer nanoparticles in mineral oil' by Matthew J. Derry et al., Chem. Sci., 2018, 9, 4071–4082.